Managed health care in the new millennium : innovative financial modeling for the 21st century - Samuels, David I. (CRC Press, 2012)
"Thoroughly exploring how capitation has evolved domestically and internationally in recent years, this book discusses actuarial assumptions and the difficulties in payers transitions from community-based underwriting to experience-based ratings. It explores what the future holds in the areas of clinical pathways and population-based risk assumption tools and approaches. It covers what happens when the underlying actuarial and risk assumptions are ignored or trivialized. The author also discusses the challenges capitation-based pricing faces from an international perspective, including Latin America and the Caribbean"--Provided by publisher.